PERAN DOSEN DALAM PELATIHAN KEWIRAUSAHAAN DI WISATA KERENG BANGKIRAI PALANGKA RAYA - Noorjaya Nahan; Muhamad Ruzaini Abdi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This community service activity aims to increase the knowledge, skills, and motivation of entrepreneurship of the community and business actors in the Kereng Bangkirai Palangka Raya Tourism area. Kereng Bangkirai is one of the leading tourist destinations in Palangka Raya City which has black water tourism attractions, river trails, local culture, and the potential of the community's creative economy. The location is in Kereng Bangkirai Village, Sebangau District, Palangka Raya City, and is known as one of the entrances to the Sebangau National Park area. The problems faced by the community around the tourist area include limited business management skills, digital marketing, product innovation, simple financial management, and tourism service strategies. Therefore, lecturers have an important role as facilitators, educators, motivators, and companions in entrepreneurship training activities. The method of the activity is carried out through lectures, discussions, business idea preparation practices, marketing simulations, and evaluation of participants' understanding. The results of the activity show that entrepreneurship training can increase participants' understanding of the importance of innovation, service, branding, financial recording, and the use of digital media to support businesses in tourist areas. This activity is expected to encourage the economic independence of local communities and strengthen the development of tourism based on community empowerment.